Routine outcome measurement in Australia. (August 2015) - Burgess, Philip; Pirkis, Jane; Coombs, Tim
Abstract Australia has been implementing routine outcome measurement in its specialized public sector mental health services for over a decade. It uses a range of clinician-rated and consumer-rated measures that are administered at set times during episodes of inpatient, ambulatory and community residential episodes of care. Routine outcome measurement is now embedded in service delivery, and data are made available in a variety of ways to different audiences. These data are used by policy-makers and planners to inform decisions about system-wide reforms, by service managers to monitor quality and effectiveness, and by clinicians to guide clinical decision-making and to promote dialogue with consumers. Consumers, carers and the general community can use these data to ensure that services are accountable for the care they deliver. This paper describes the status quo in Australia with respect to routine outcome measurement, discusses the factors that led to its successful implementation, and considers the steps that are necessary for its continued development.